Effectiveness of Emergent Ad Hoc Coordination Groups in Public Health Emergencies. Issue 1 (7th May 2021) - Kim, Yushim; Lee, Kangbae; Oh, Seong Soo; Park, Heejin
Abstract: Whether emergent groups positively or negatively influence a disaster response remains inconclusive in the literature. We analyzed the effect of an emergent group on two interorganizational networks for information communication and resource coordination during a public health emergency response. Using the 2015 Middle East Respiratory Syndrome (MERS) Coronavirus in Korea as a study case, we identified an ad hoc entity that appeared in both networks. This emergent group, which consists of government officials and public health specialists, directed and coordinated organizations at the center of the response networks. We found that the emergent group positively contributed to efficient information communication but had no effect on the resource network's efficiency. Our interpretation is that the ad hoc entity was filling relational gaps in the information network, but was redundant in the resource network.